Development of 6LoWPAN in Embedded Wireless System. (2016) - Chalappuram, Amitha; Sreesh, P.R.; George, Juney M.
Abstract: In the proposed system, implementation of the low power sensor nodes is proposed. 6LoWPAN is an acronym of IPv6 over Low power Wireless Personal Area Network was developed to enable the Wireless Embedded Internet by simplifying IPv6 functionality, defining very compact header formats and taking the nature of wireless networks into account. Our solution contains two types of nodes Wireless Sensor Node and Border Router/Gateway Node. Wireless Sensor Node: These nodes have sensors integrated and are used to gather the information and send to the Border Router/Gateway Node. They create a mesh network among them, forwarding the packets of other nodes in order to make the information reach the Border Router/Gateway Node. Each Wireless Sensor Node is equipped with a 6LoWPAN (802.15.4) radio, sensors and a battery. It can be either a microcontroller based or Linux based embedded platforms. Border Router/Gateway Node: This node takes the information sent by the Wireless Sensor Nodes and sends it to the Tunneling IPv4 / IPv6 server by using the Ethernet IPv4 interface. Each Border Router/Gateway Node is equipped with a Linux based Single Board Computer, 6LoWPAN (802.15.4) radio and an Ethernet interface and a battery.